Natural Memory Beyond the Storage Model: Repression, Trauma, and the Construction of a Personal Past - Axmacher, Nikolai; Do Lam, Anne T.; Kessler, Henrik; Fell, Juergen (Frontiers in Human Neuroscience, 2010)
Naturally occurring memory processes show features which are difficult to investigate by conventional cognitive neuroscience paradigms. Distortions of memory for problematic contents are described both by psychoanalysis (internal conflicts) and research on post-traumatic stress disorder (external traumata). Typically, declarative memory for these contents is impaired – possibly due to repression in the case of internal conflicts or due to dissociation in the case of external traumata – but they continue to exert an unconscious pathological influence: neurotic symptoms or psychosomatic disorders after repression or flashbacks and intrusions in post-traumatic stress disorder after dissociation. Several experimental paradigms aim at investigating repression in healthy control subjects. We argue that these paradigms do not adequately operationalize the clinical process of repression, because they rely on an intentional inhibition of random stimuli (suppression). Furthermore, these paradigms ignore that memory distortions due to repression or dissociation are most accurately characterized by a lack of self-referential processing, resulting in an impaired integration of these contents into the self. This aspect of repression and dissociation cannot be captured by the concept of memory as a storage device which is usually employed in the cognitive neurosciences. It can only be assessed within the framework of a constructivist memory concept, according to which successful memory involves a reconstruction of experiences such that they fit into a representation of the self. We suggest several experimental paradigms that allow for the investigation of the neural correlates of repressed memories and trauma-induced memory distortions based on a constructivist memory concept.